3 Visit-to-visit Blood Pressure Variability Varies by Age Groups. (November 2017) - Lukito, A.A.; Thengker, A.; Hadi, M.W.; Christiani, A.; Damay, V.A.; Lim, H.
Abstract : Background: Aging and depressed spontaneous baroreceptor sensitivity (sBRS) and blood pressure variability (BPV) have been linked to negative cardiovascular outcomes. Visit-to-visit blood pressure (BP) variability is a predictor of an increased risk of all-cause mortality, stroke, left ventricular diastolic dysfunction, and cognitive impairment among diverse populations. However the relationship between BPV and age has not been clearly described by age groups. Method: Visit-to-visit BP data were collected from our institution's medical record department, which documented hypertensive patients in January-December 2015 who regularly attended follow-up visits. The BP data were tracking back until the first visit. The BPVs of these patients were calculated using standard deviation (SD) and average reading variability (AVR) in each follow up visit. AVR is defined as an average of absolute differences consecutive readings. Result: There were 131 subjects who met the inclusion criteria. There were 51.9% (68) male subjects with mean age of 58.61 (33–91 yo), 31% were 65 years or older and 15% were 75 years or older. The overall BPV data showed mean systolic BP (SBP)-AVR of 14.45 mmHg, mean diastolic BP (DBP)-AVR of 7.63 mmHg, mean SBP-SD of 15.36 mmHg and mean DBP-SD of 8.39mmHg. Bivariate analysis using Pearson's test showed statistically a significant negative correlation between DBP-AVR and age (p < 0.05, r: −0.20) and a negative correlation between DBP-SD and age (p < 0.05, r: −0.22). Moreover, in the age groups with cut-off 65 year-old, the mean SBP-ARV was 11.5 mmHg and mean DBP-ARV was7.65 mmHg in ≥65 year-old and the mean SBP-ARV was 11.3 mmHg and mean DBP-ARV was 8.68 mmHg in < 65 year-old hypertensive subjects, while the mean SBP-SD was 11.9 mmHg and mean DBP-SD was 8.44 mmHg ≥65 year-old and the mean SBP-SD was 11.6 mmHg and mean DBP-SD was 9.18 mmHg in <65 year-old hypertensive subjects. While in the age groups with cut-off 75 year-old, the mean SBP-ARV was 11.6 mmHg and mean DBP-ARV was 7.77 mmHg in ≥75 year-old and, the mean SBP-ARV was 11.3 mmHg and mean DBP-ARV was 8.47 mmHg in <75 year-old hypertensive subjects, while the mean SBP-SD was 12.3 mmHg and mean DBP-SD was 8.69 mmHg ≥75 year-old and the mean SBP-SD was 11.6 mmHg and mean DBP-SD was 9.0 mmHg in <75 year-old hypertensive subjects. Data was analyzed with comparative independent-samples, and showed significant differences of DBP-ARV (p = 0.012) and DBP-SD (p = 0.02) in the age groups with cut-off 65 year-old, In contrary, there was significant difference of SBP-SD (p = 0.034) in the age groups with cut-off 75 year-old. Conclusion: This study found that ageing attenuated the diastolic blood pressure variability. In the age group subjects, diastolic BPV was lower in ≥65 year-old and systolic BPV was lower in ≥75 year-old hypertensive subjects. These findings confirmed the effect of ageing in the long-term visit-to-visit BPV.